Borehole fibre-optic seismology inside the Northeast Greenland Ice Stream ... - Fichtner, Andreas; Hofstede, Coen; Gebraad, Lars; Zunino, Andrea; Zigone, Dimitri; Eisen, Olaf (ETH Zurich, 2023)
Ice streams are major contributors to ice sheet mass loss and sea level rise. Effects of their dynamic behaviour are imprinted into seismic properties, such as wave speeds and anisotropy. Here, we present results from a distributed acoustic sensing (DAS) experiment in a deep ice-core borehole in the onset region of the Northeast Greenland Ice Stream, with focus on phenomenological and methodological aspects. A series of active seismic surface sources produced clear recordings of the P and S wavefield, including internal reflections, along a 1500 m long fibre-optic cable that was placed into the borehole. The combination of nonlinear traveltime tomography with a firn model constrained by multimode surface wave data, allows us to invert for P and S wave speeds with depth-dependent uncertainties on the order of only 10 m s-1, and vertical resolution of 20-70 m. The wave speed model in conjunction with the regularly spaced DAS data enable a straightforward separation of internal upward reflections followed by a ... : Geophysical Journal International, 235 (3) ...